THE EFFECT OF TYPE ORGANIC SUPPLEMENTS ON THE GROWTH ORCHID Phalaenopsis hybrid SUBCULTURE IN MS MEDIA - mita elfini; asnawati .; agustina listiawati (Fakultas Pertanian Universitas Tanjungpura, 2020)
Culture media is one of the main factors that determine the success propagation with in vitro culture. Basic media in vitro culture such as Murashige and Skoog (MS) with the addition of complex organic compounds can increase plantlet growth in tissue culture.This study aims to determine the effect of the addition various types organic supplements to MS media on the growth of Phalaenopsis hybrid sub-culture in vitro. This study began from 14 August to 14 December 2018 in the Biotechnology Laboratory, Agriculture Faculty, Tanjungpura University.The methodology that was in study used Completely Randomized Designed (CRD) consisted of 6 treatments, 4 treatments and each replications there were 4 plant sample. The treatment is as follows : U= MS; V= MS+ Coconut Water Supplement; W= MS+Beans Sprout Supplement; X=MS+Carrot Supplement; Y= MS+ Aloe Vera Supplement and Z= MS+ Tomatoes supplement for each treatment 100 ml / L of organic supplements were added. The variable observed in this study were increment number of leaves (sheet), increment number of root (sheet), Number of shoots ( Shoots) and time formed budding (Weeks after planting). The research showed that provision of a type various organic supplements on MS media has not been able to improve the growth of the hybrid Phalaenopsis orchid subculture on all observed variables. Key Words :In Vitro, Media Murashige and Skoog (MS), Orchid, Organic supplement, Phalaenopsis hybrid.